2020
DOI: 10.1142/s1793292020500897
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doped UiO-66 Combined with ZnIn2S4 for Adsorption and Degradation of RhB Under Visible Light

Abstract: Novel ZnIn2S4/FeUiO-66 (ZFeU) photocatalyst with different proportion of FeUiO-66 has been successfully prepared by a facile one-pot solvothermal reaction. The as-synthesized nanocomposites have been thoroughly characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform-infrared spectroscopy (FT-IR), UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS), Brunauer–Emmett–Teller (BET) characterization, photoluminescence (PL) analysis and electrochemical impedance spectrum (EIS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the spectra of pure ZnO, the peaks over the range of 600–400 cm −1 were attributed to the fundamental vibration of Zn–O [ 59 ]. In the FT-IR spectra of pure ZnIn 2 S 4 , the observed peaks were ascribed to the surface water molecules and hydroxyl groups [ 60 ]. Compared with the spectra curves in Figure 2 N, the FT-IR peaks of ZnO/ZnIn 2 S 4 heterojunctions were completely in accord with those of pure ZnO and ZnIn 2 S 4 , which further confirmed the successfully synthesized ZnO/ZnIn 2 S 4 heterojunctions.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectra of pure ZnO, the peaks over the range of 600–400 cm −1 were attributed to the fundamental vibration of Zn–O [ 59 ]. In the FT-IR spectra of pure ZnIn 2 S 4 , the observed peaks were ascribed to the surface water molecules and hydroxyl groups [ 60 ]. Compared with the spectra curves in Figure 2 N, the FT-IR peaks of ZnO/ZnIn 2 S 4 heterojunctions were completely in accord with those of pure ZnO and ZnIn 2 S 4 , which further confirmed the successfully synthesized ZnO/ZnIn 2 S 4 heterojunctions.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of chemical synthesis techniques, MOFs can be used as matrices for various functional species (e.g., nanoparticles), offering the possibility of developing novel composite materials. [239][240][241] It has been shown that some MOFs undergo the photo-Fenton reaction under light due to the synergistic effect of catalytically active sites, and in particular, Fe based or Fe doped MOFs can be used as non-homogeneous photocatalysts. 241,242 There are currently two methods for the synthesis of functional material/MOF composites: first, the pre-synthesized functional material is used for stabilization by surfactants and later encapsulated during MOF growth, and second, the synthesized MOF is used as a matrix and the functional material is synthesized in its cavity.…”
Section: Loaded Mof-based Materialsmentioning
confidence: 99%